(untitled) (Global Journal of Science Frontier Research, 2015)
The paper is concerned with two dimensional deformation in a homogeneous, transversely isotropic thermoelastic solids without energy dissipation and with two temperatures due to various sources. Assuming the disturbances to be harmonically time-dependent, the transformed solution is obtained in the frequency domain. The application of a time harmonic concentrated and distributed sources have been considered to show the utility of the solution obtained. The transformed components of displacements, stresses and conductive temperature distribution so obtained are inverted numerically using a numerical inversion technique. Effect of anisotropy and two temperature on the resulting expressions are depicted graphically.